VALIDATION OF THE ONLINE COPING INVENTORY FOR THE LGBTQ PEOPLE IN MALAYSIA - Azmawaty Mohamad Nor; Harris Shah Abd Hamid; Muhammad Ashraff Ahmad (Journal of Islamic, Social, Economics and Development, 2022)
With the rapid use of the internet, the online platform became more accessible as a tool to cope with daily stressors. The Lesbian, Gay, Bisexual, Transgender, and Queer (LGBTQ) community use this platform to obtain information, social connection, and even sexual relations for self-identification, information exchange, and social support despite various social, legal, cultural, and religious restrictions in Malaysia. Many studies had shown the importance of online coping but mainly focused on a specific online coping strategy rather than a consolidated view especially for the LGBTQ people in Malaysia. This study aimed to explore the psychometric properties of the Online Coping Strategy as there are limited instruments that measure online coping strategies and are targeted for this population. The sample consisted of 189 LGBTQ individuals through a survey design study. The confirmatory factor analysis results showed that the three-factor model had acceptable values for the goodness of fit indices indicating the stability of the measurement model, with good validity and reliability standing. The study found that the instrument had stable psychometric properties for practical use to measure online coping strategies among LGBTQ individuals in Malaysia. Further research is required to refine and verify its psychometric properties and credentials for different populations and settings.